Solubility Measurement and Correlation of Alprazolam in Carbon Dioxide With/Without Ethanol at Temperatures from 308 to 338 K and Pressures from 120 to 300 Bar - Rojas-Sepulveda, A (American Chemical Society, 2024)
This research investigated the solubility of alprazolam in supercritical carbon dioxide (scCO2) with the addition of ethanol as a cosolvent. The solubility was examined at various pressures (ranging from 120 to 300 bar) and temperatures (ranging from 308 to 338 K). The solubility of alprazolam in scCO2 ranged from 0.027 × 10-4 to 0.632 × 10-4. When ethanol was used as a cosolvent, the solubility increased to a range of 0.157 × 10-4 to 1.660 × 10-4 (with 1 mol % ethanol) and 0.449 × 10-4 to 3.167 × 10-4 (with 3 mol % ethanol). Under the specified operating parameters, the highest solubility of alprazolam was achieved in the ternary system (with 3 mol % ethanol) at 120 bar and 338 K. This solubility was 16.63 times higher than when using pure scCO2 under the same circumstances. Several semiempirical correlations were used to compute the solubility of alprazolam in supercritical carbon dioxide. These models yielded similar average absolute relative deviations ranging from 7.0 to 8.40%. The findings demonstrated the superiority of the Kumar-Johnston model in binary systems (with an average absolute relative deviation of 7.0%) and the Garlapati-Madras model in ternary systems (with an average absolute relative deviation of 6.19%) compared to alternative models. © 2024 American Chemical Society